Signifikansi Sekolah Mewujudkan Siswa Berkarakter Melalui Bijak Bergawai di SD Negeri 10 Pangkalpinang - Ria Anggreni (EDOIS: Journal of Islamic Education, 2023)
Gadgets have become a device that is commonly used, even by elementary school-age children. As a form of addressing the phenomenon of the use of devices by children in depth, researchers conducted research at SD Negeri 10 Pangkalpinang. This research aims to: 1) know the form of character building in students at SD Negeri 10 Pangkalpinang through the wise gadget program; 2) know the significance of wise habituation in using gadgets with the character of students at SD Negeri 10 Pangkalpinang. This research uses qualitative methods; data collection techniques are carried out by means of observation, interviews, and documentation. Reducing, presenting, verifying, and validating the collected data are all parts of data analysis. The results showed: 1) The form of character building in SD Negeri 10 Pangkalpinang students through the wise program includes vision and mission, curriculum, lesson plans, learning activities, self-development, P5, and extracurricular activities; 2) The significance of wise habituation in using gadgets with the character of students of SD Negeri 10 Pangkalpinang, including the support of facilities and infrastructure, school achievements, educators and education personnel, and the condition of students who are quite good at using gadgets. The use of technology-based devices can still balance good character so that students are wiser when utilizing devices in everyday life. The characters that are realized in the wise gadget program include religion (morals), integrity, and independence. Researchers see that the school has made efforts to overcome the negative impact of gadgets. Bijak Bergawai at SD Negeri 10 Pangkalpinang has been able to address the negative impact of gadgets that have an influence on student character, so researchers conducted further research with the title Significance of Schools in Realizing Students with Character through Bijak Bergawai at SD Negeri 10 Pangkalpinang.